Antimicrobial resistance, virulence gene profile and molecular typing of Staphylococcus aureus isolates from dairy cows in Xinjiang Province, northwest China - Dan, Meng; Yehui, Wu; Qingling, Meng; Jun, Qiao; Xingxing, Zhang; Shuai, Ma; Kuojun, Cai; Jinsheng, Zhang; Zibing, Cheng; Zaichao, Zhang; Xuepeng, Cai (Journal of Global Antimicrobial Resistance, 2019)
•MRSA had a high percentage of multidrug-resistant strains compared with MSSA.•The frequency of different virulence genes varied between MSSA and MRSA.•The S. aureus strains could be divided into 2 SCCmec types, 3 agr types, 4 spa types and 14 STs.•ST9-t1939-agrI and ST1-SCCmecI-t1939-agrI were the main genotypes of MSSA and MRSA, respectively, from dairy cows.•STX is a novel genotype identified for the first time in this study. Staphylococcus aureus (SA) is a major pathogen causing dairy cow mastitis and endometritis. Recently, animal-derived SA strains pose a serious public-health threat. However, little is known about antimicrobial resistance and virulence factors of SA isolated from dairy cows in Xinjiang, China. In this study, antimicrobial resistance, virulence gene profiles and genotypes of SA from clinical mastitis and endometritis in dairy cows were investigated. A total of 337 clinical samples (186 milk samples from clinical mastitis cases and 151 endometritis swab samples) were collected from 15 large-scale dairy farms and were screened for SA. All SA isolates were subjected to antimicrobial susceptibility testing, detection of virulence genes and molecular typing. A total of 155 SA strains were isolated; 22 (14.2%) were methicillin-resistant S. aureus (MRSA). Resistance of MRSA isolates was significantly higher than that of methicillin-susceptible S. aureus (MSSA). The percentage of virulence genes varied between MSSA and MRSA. The strains could be divided into two SCCmec types (I and IVa), three agr types (I, II and III) and four spa types (t779, t2883, t13751 and t1939). MLST identified 14 sequence types, among which ST1 and ST9 had relatively high detection rates. These findings revealed that ST9-t1939-agrI was the main genotype of MSSA, whilst ST1-SCCmecI-t1939-agrI was the main genotype of MRSA from dairy cows. More significantly, a novel ST (STX) was identified for the first time. The majority of SA strains from dairy cows were multidrug-resistant and carried multiple virulence genes, posing a potential public-health risk.